Artykuły lwowskiej konfederacji wojska koronnego z 1622 roku - Antos, Patryk (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The objective of this paper is to present a very rare document – the articles of the Lwów confederation. Only a few such documents survived and only as copies because, after the conclusion of a confederation, its articles were publicly burned. Publication of these documents will allow the readers for familiarizing themselves with an interesting contribution to the knowledge of the military history of the Polish-Lithuanian Commonwealth, without the need for a preliminary survey in the holdings of The Princes Czartoryski Library in Cracow.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne